PENGEMBANGAN MODUL PEMBELAJARAN GENETIKA BERBASIS FENOMENA LOKAL - Muhammad Luthfi Hidayat, Suratsih, Victoria Henuhili, Tutiek Rahayu, dan (Jurnal Cakrawala Pendidikan, 2010)
Abstract This study aimed to find out the gene inheritance pattern of the gembel hair in a family in Solomerto Village, Solomerto District, Wonosobo Regency, to design a local phenomenon based module for genetics learning, and to investigate the readability of the learning module. This study was based on the data of the family tree map of a family with the gembel hair inheritance that could be traced to three generations so that this fulfilled the requirements to trace the gene inheritance. The data on the gembel hair inheritance were collected through observations and interviews. The data were then analyzed to find out the characteristic inheritance by making a map of the family tree and determining the genotype possibility of each family member. To investigate the readability of the module, 20 students of SMA Negeri 8 Yogyakarta were selected as the sample. The data were analyzed using the qualitative descriptive technique. The results of the study on the basis of the family tree map showed that the gembel hair gene inheritance was determined by the recessive autosomal gene. The students gave positive responses to the local phenomenon based learning module in terms of the material coverage, the material explanation, the number of test items, the item difficulty level, the instruction, and the key answers. Keywords: genetics, local phenomenon, learning module, gembel hair